2022
DOI: 10.3390/cryst12040506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Deformation Annealing on Structure and Properties of Nickel-Enriched Ti-Ni Shape Memory Alloy Deformed in Various Initially Deformation-Induced Structure States

Abstract: The effect of post-deformation annealing (PDA) of nickel-enriched Ti-50.9 at.% Ni shape memory alloy deformed in various initially deformation-induced structure states on the structure and properties was studied. The phase composition, temperature ranges of martensitic transformations and structure were studied using X-ray diffractometry and TEM. Mechanical and functional properties were determined using Vickers hardness tests and thermomechanical method using a bending mode for recovery strain inducing. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It can be consequently concluded that the dynamic recovery and polygonization processes in nickel-enriched NiTi SMA in the same thermomechanical conditions are less developed compared to those of an equiatomic NiTi alloy. This can be explained by the retarding effect of the finely dispersed Ni 4 Ti 3 phase particles that were precipitated during dynamic strain aging [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be consequently concluded that the dynamic recovery and polygonization processes in nickel-enriched NiTi SMA in the same thermomechanical conditions are less developed compared to those of an equiatomic NiTi alloy. This can be explained by the retarding effect of the finely dispersed Ni 4 Ti 3 phase particles that were precipitated during dynamic strain aging [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present work continues the previous studies, and it is focused on the investigation of the effect of bi-axial deformation on the structural phase state and properties of bulk nickel-enriched NiTi SMA. In these alloys, deformation in the temperature range of dynamic polygonization is accompanied by dynamic strain aging with the precipitation of Ni 4 Ti 3 particles, which cannot occur in non-aging equiatomic NiTi SMA, and it has a great impact on the structure’s formation and properties [ 18 , 19 , 20 , 21 ]. The precipitated particles restrict the grain growth, however, they can lead to earlier sample destruction compared to that of equiatomic alloy and the accumulation of a lowered value of true strain.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, in itself, obtaining a mixed nanograined and nanosubgrained structure in titanium nickelide bulk samples is an important scientific and technological result [27][28][29]. During pre-aging for 1 h, the growth of Ti 3 Ni 4 phase particles proceeds less intensively than that after pre-aging for 5 h [30][31][32]. Thus, during QC ECAP, finer Ni 4 Ti 3 particles after pre-aging for 1 h provide higher resistance to grain boundary migration and the formation of a finer matrix structure, while after pre-aging for 5 h coarser and rarer Ti 3 Ni 4 particles inhibit matrix structure refinement to a lesser extent.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Binary NiTi alloys provide remarkable shape memory characteristics in combination with extraordinary mechanical properties; therefore, they are the most widely used shape memory alloys (SMAs) for industrial purposes. Severe plastic deformation (SPD) is commonly applied to NiTi SMA for the formation of an ultrafine-grained (UFG) structure, e.g., submicrocrustalline (SMCS) and nanocrystalline structures (NCSs), and to improve the combination of its properties [4][5][6][7][8][9][10]. However, the formation of an NCS in bulk NiTi samples after SPD is a difficult scientific challenge [11,12].…”
Section: Introductionmentioning
confidence: 99%